2022
DOI: 10.3390/ijms23148000
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Delta-9-tetrahydrocannabinol (THC) Alters the Expression of miR-122-5p and Its Target Igf1r in the Adult Rat Ovary

Abstract: As cannabis use during pregnancy increases, it is important to understand its effects on the developing fetus. Particularly, the long-term effects of its psychoactive component, delta-9-tetrahydrocannabinol (THC), on the offspring’s reproductive health are not fully understood. This study examined the impact of gestational THC exposure on the miRNA profile in adult rat ovaries and the possible consequences on ovarian health. Prenatal THC exposure resulted in the differential expression of 12 out of 420 evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…The authors propose that these epigenetic modifications could contribute to addiction vulnerability later in life [56]. Prenatal THC exposure can also lead to the differential expression of micro RNA (miRNAs) [57]. In one study, prenatal THC exposure was associated with the upregulation of miR-122-5p and the resultant downregulation of insulin-like growth factor 1 receptor (Igf1r) [57].…”
Section: Cannabis-induced Epigenetic Effectsmentioning
confidence: 99%
“…The authors propose that these epigenetic modifications could contribute to addiction vulnerability later in life [56]. Prenatal THC exposure can also lead to the differential expression of micro RNA (miRNAs) [57]. In one study, prenatal THC exposure was associated with the upregulation of miR-122-5p and the resultant downregulation of insulin-like growth factor 1 receptor (Igf1r) [57].…”
Section: Cannabis-induced Epigenetic Effectsmentioning
confidence: 99%
“…Moreover, several studies proved that using antidepressants during gestational age would induce birth defects, especially for congenital heart disease. For example, Sun et al (2022) indicated that the use of maternal antidepressant 3 months before pregnancy and early pregnancy exposure to an antidepressant would elevate the risk of congenital heart disease among the offspring. In addition, intrauterine fluoxetine exposure was associated with several congenital malformations (RR = 1.18, 95% CI = 1.08-1.29).…”
Section: Antidepressantsmentioning
confidence: 99%
“…Indeed, poor placental function has been proven to be associated with obesity, hypertension, and diabetes in later adult life. While García-Otero et al (2022) demonstrated an observational study to identify that intrauterine exposure to HIV and antiretroviral therapy were not associated with cardiovascular changes from fetal development to infant growth, they did not measure the longterm outcomes of the cardiovascular system.…”
Section: Antiretroviral Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…CBD alone was shown to suppress inflammation in an animal model of EAE by modulating several miRNAs [ 127 ]. It was shown that prenatal THC exposure enhanced miR-122-5p; reduced the expression of its target, insulin-like growth factor 1 receptor (Igf1r), in adult rat ovary follicular cells; and caused follicular apoptosis [ 169 ]. In another study, activation of CB 2 by a specific agonist (AM1241) was suggested to protect dopaminergic neurons in Parkinson’s disease animals.…”
Section: Regulation Of Micrornas and Cannabinoid Receptorsmentioning
confidence: 99%